Analysis of secA1 Gene Sequences for Identification of Nocardia Species - Conville, Patricia S. (American Society for Microbiology, 2006)
Molecular methodologies, especially 16S rRNA gene sequence analysis, have allowed the recognition of many new species of Nocardia and to date have been the most precise methods for identifying isolates reliably to the species level. We describe here a novel method for identifying Nocardia isolates by using sequence analysis of a portion of the secA1 gene. A region of the secA1 gene of 30 type or reference strains of Nocardia species was amplified using secA1-specific primers. Sequence analysis of 468 bp allowed clear differentiation of all species, with a range of interspecies similarity of 85.0% to 98.7%. Corresponding 16S rRNA gene sequences of a 1,285-bp region for the same isolates showed a range of interspecies similarity of 94.4 to 99.8%. In addition to the type and reference strains, a 468-bp fragment of the secA1 gene was sequenced from 40 clinical isolates of 12 Nocardia species previously identified by 16S rRNA gene sequence analysis. The secA1 gene sequences of most isolates showed >99.0% similarity to the secA1 sequences of the type or reference strain to which their identification corresponded, with a range of 95.3 to 100%. Comparison of the deduced 156 amino acid sequences of the SecA1 proteins of the clinical isolates showed between zero and two amino acid residue differences compared to that of the corresponding type or reference strain. Sequencing of the secA1 gene, and using deduced amino acid sequences of the SecA1 protein, may provide a more discriminative and precise method for the identification of Nocardia isolates than 16S rRNA gene sequencing.